2021
DOI: 10.1200/jco.2021.39.15_suppl.7565
|View full text |Cite
|
Sign up to set email alerts
|

Phased variants improve DLBCL minimal residual disease detection at the end of therapy.

Abstract: 7565 Background: Detection of circulating tumor DNA (ctDNA) has prognostic value in diverse tumors, including DLBCL. Despite uses for assessing molecular response to therapy, current methods using immunoglobulin or hybrid-capture sequencing have suboptimal sensitivity, particularly when disease-burden is low. This contributes to a high false negative rate at key milestones such as at the end of therapy (EOT; Kumar A, ASH 2020). We explored the utility of detecting multiple mutations (phased variants, PVs) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In situations with extremely low tumor burden, particularly during treatment and at the end of lymphoma therapy, current methods are still limited by suboptimal sensitivity [44][45][46]. Prior studies have used somatic mutations identified on both DNA strands to further decrease ctDNA detection limits ('duplex sequencing').…”
Section: Technical Considerations For Ctdna Detection and Quantificationmentioning
confidence: 99%
“…In situations with extremely low tumor burden, particularly during treatment and at the end of lymphoma therapy, current methods are still limited by suboptimal sensitivity [44][45][46]. Prior studies have used somatic mutations identified on both DNA strands to further decrease ctDNA detection limits ('duplex sequencing').…”
Section: Technical Considerations For Ctdna Detection and Quantificationmentioning
confidence: 99%
“…Both pretreatment levels and dynamic changes in circulating tumor DNA (ctDNA) have been associated with clinical outcomes, and in many studies, ctDNA outperforms traditional response assessment tools. 1 , 2 , 3 Newer panel‐based approaches (CAPP‐Seq, PhasED‐Seq) appear to have improved sensitivity compared to immunoglobulin‐based high‐throughput sequencing (IgHTS). 4 , 5 There is growing interest in using ctDNA to guide response‐adapted treatment approaches in DLBCL and ctDNA techniques that maximize sensitivity while retaining excellent specificity are needed to optimally guide such strategies.…”
mentioning
confidence: 99%